Breath-by-breath measurement of exhaled ammonia by acetone-modifier positive photoionization ion mobility spectrometry via online dilution and purging sampling - Lu Wang; Dandan Jiang; Lei Hua; Chuang Chen; Dongming Li; Weiguo Wang; Yiqian Xu; Qimu Yang; Haiyang Li; Song Leng (Elsevier, 2023)
Exhaled ammonia (NH3) is an essential noninvasive biomarker for disease diagnosis. In this study, an acetone-modifier positive photoionization ion mobility spectrometry (AM-PIMS) method was developed for accurate qualitative and quantitative analysis of exhaled NH3 with high selectivity and sensitivity. Acetone was introduced into the drift tube along with the drift gas as a modifier, and the characteristic NH3 product ion peak of (C3H6O)4NH4+ (K0 = 1.45 cm2/V·s) was obtained through the ion-molecule reaction with acetone reactant ions (C3H6O)2H+ (K0 = 1.87 cm2/V·s), which significantly increased the peak-to-peak resolution and improved the accuracy of exhaled NH3 qualitative identification. Moreover, the interference of high humidity and the memory effect of NH3 molecules were significantly reduced via online dilution and purging sampling, thus realizing breath-by-breath measurement. As a result, a wide quantitative range of 5.87-140.92 μmol/L with a response time of 40 ms was achieved, and the exhaled NH3 profile could be synchronized with the concentration curve of exhaled CO2. Finally, the analytical capacity of AM-PIMS was demonstrated by measuring the exhaled NH3 of healthy subjects, demonstrating its great potential for clinical disease diagnosis.